Two new species of snailfishes of the genus Careproctus (Cottoidei: Liparidae) from the western North Pacific Ocean with a range extension of Careproctus brevipectoralis - Kai, Yoshiaki; Endo, Hiromitsu; Tashiro, Fumihito; Nakayama, Naohide (Zootaxa, 2021)
Three snailfish species of Careproctus (Cottoidei: Liparidae), including two new species, are described from the deep Pacific Ocean off northern Honshu Island, Japan. Careproctus cyanogladius sp. nov., collected from the depths of 2,698–3,223 m, can be distinguished from congeneric species by having the following combination of characters: vertebrae 63; dorsal-fin rays 57–58; anal-fin rays 50; principal caudal rays 7; pectoral-fin rays 29–31; pectoral fin without a notch; uppermost pectoral-fin base below a horizontal through posterior margin of maxillary; pelvic disk oval; chin pores well separated; teeth simple; pyloric caeca 6–10; body pale blue or gray when fresh. The other new species, Careproctus orri sp. nov., collected from depths of 640–808 m, can be distinguished from congeneric species by having the following combination of characters: vertebrae 58–60; dorsal-fin rays 52–53; anal-fin rays 47–49; pectoral-fin rays 34–35; pectoral fin with a distinct notch; cephalic pores 2-6-7-2, chin pores single, unpaired; gill slit extending ventrally to 5th or 6th pectoral-fin ray; teeth strongly trilobed; peritoneum dark, stomach white. In addition, one specimen of Careproctus brevipectoralis Chernova, Thiel & Eidus, 2020 was newly collected from Japan, and is redescribed here in detail with comments on intraspecific variations.